BIOAKUMULASI DAN ANALISIS RISIKO KESEHATAN MASYARAKAT DARI PENCEMARAN LOGAM BERAT Pb DAN Cd PADA IKAN YANG DITANGKAP DI TUKAD BADUNG, DENPASAR - Palgunadi, Ni Putu Gita Saraswati; Purnama, I Gede Herry (ARCHIVE OF COMMUNITY HEALTH, 2022)
Tukad Badung is a river that crosses Badung and Denpasar Regencies. 3 locations are often used for fishing, namely Tukad Korea, Fishing Park, and Muara Dam. Previous research showed that this river polluted by Pb and Cd. This research is a descriptive observational study with a field survey method on levels of lead and cadmium in fish that have been caught in Tukad Badung and survey of fish consumption habits to predict public health risks. This study uses an Environmental Health Risk Analysis (EHRA) approach. Fish samples selection used purposive sampling and convenient sampling for respondent selection. Laboratory results showed that the levels of Pb in mujair ranged from 0.1104-0.5012 ppm, and in Tilapia ranged from 0.0928-0.4462 ppm. The average lead in the two types of fish has exceeded the maximum limit of Pb in fish as regulated in PerBPOM No.23.2017. Health risk calculations showed the value of EDI show that the daily intake of Pb is classified as high risk. THQ value of Pb indicates a low level of non-carcinogenic risk. TR value for Pb indicates a low level of carcinogenic risk. Meanwhile, the value of EDI, THQ, HI and TR of Cd could not be calculated. Keywords:  Lead, Cadmium, Fish, Environmental Health Risk Assessment